A Review of Spreadable Media: Creating Value and Meaning in a Networked Culture - Laura M. Gorham (Journal of Applied Communications, 2016)
Book review: Spreadable Media: Creating Value and Meaning in a Networked Culture by Henry Jenkins, Sam Ford, and Joshua Green.
Keywords: book review; Online Media; Media Content; Participatory Culture; Emerging Media